Pengaruh Work-Life Balance terhadap Job Stress dan Job Performance melalui Employee Engagement pada Karyawan RS XYZ - Windi Setyoningtias; Dewie Tri Wijayati Wardoyo (Universitas Negeri Surabaya, 2026)
High work pressure, heavy workloads, and the demand for fast and accurate service in the healthcare sector make the issues of work-related stress and employee performance a key concern in human resource management. This study aims to analyze the influence of work-life balance on job stress and job performance through employee engagement among employees at health sector. Using a quantitative approach with a saturated sampling technique, 63 employees at health sector were included as the sample. Data were collected through questionnaires and interviews, then analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method via the SmartPLS 3.2.9 software. The results of this study indicate that work-life balance has a significant negative effect on job stress and a significant positive effect on employee engagement. Meanwhile, work-life balance does not have a significant direct effect on job performance. Employee engagement was found to have a significant negative effect on job stress and a significant positive effect on job performance. Furthermore, employee engagement was found to mediate the effect of work-life balance on job stress and also mediate the effect of work-life balance on job performance. The implication of this study indicate that health sector need to pay attention to work-life balance as part of their human resource management strategy to reduce job stress and improve job performance. The role of employee engagement is very important in strengthening the positive effects of work-life balance on productivity.